PROBLEM BASED LEARNING DAN LKPD : STRATEGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII-B SMPN 56 SURABAYA - Tanjung Sari, Tiara Rahma; Purnomo, Nugroho Hari; Yudiana, Arin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This class action research seeks to address the issue of inadequate learning outcomes among students in class VIII-B at SMPN 56 Surabaya, specifically in the context of social studies related to geographical conditions and their impact on natural diversity and community life. The study employed a Problem-Based Learning (PBL) model, which was integrated with Learner Worksheets (LKPD), involving 35 students as participants. Data were collected through various methods, including tests, observations, and documentation. Data analysis revealed a notable improvement in student performance following the first cycle, with learning outcomes reaching 66% and an average score of 72. This was further enhanced in the second cycle, where learning outcomes increased to 86% with an average score of 83. Furthermore, the observations revealed an increase in both student engagement and enthusiasm throughout the learning process. As a result, it can be inferred that the application of the PBL learning model in conjunction with LKPD constitutes an effective strategy for improving student learning outcomes in social studies.